Newman polémiste et satiriste - Keith Beaumont (Cahiers Victoriens et Edouardiens)
Newman is widely recognized in the English-speaking world as one of its great satirical authors (though it has to be admitted that his subtle irony sometimes escapes the translators of his work into other languages, notably French !). He admirably illustrates also that literary genre so prized by our Victorian ancestors, polemic. The source of these two characteristics is to be sought in the circumstances of the composition of most of his published works, namely the various struggles in which he participated throughout his long life. But irony, satire and his typically English form of self-deprecating humour also take on in Newman’s work a psychological and even a spiritual function.This article seeks to illustrate and to analyse these various features in four of his writings : The Tamworth Reading Room of 1840 ; Lectures on the Present Position of Catholics of 1851 ; Discourses on University Education of 1852 (which will become in 1873 the first part of The Idea of a University) ; and the Apologia pro vita sua, particularly in its now little known first edition of 1864 but also in the much revised version of 1865 which forms the basis of all subsequent editions.